TINJAUAN KUALITAS GENTENG BERGELASIR PRODUK UNIT UJI DI UNIVERSITAS NEGERI YOGYAKARTA BERDASARKAN HASIL UJI LABORATORIUM BAHAN BANGUNAN - inotek, Darmono (Universitas Negeri Yogyakarta, 2009)
AbstractThis Unit UJI Program aims to: (1) add income for UNY and itsacademic members, (2) supply facilities for the lecturers and students toconduct research and community service activities, (3) prepare new jobs inthe glazuur material industry sector, and (4) give opportunities and workingexperience (new work field) for the UNY students.The development of the glazuur material products applies certainchemical reaction principles affected by composition (chemical substanceconcentration), reaction temperature, chemical characteristic, and physicalcharacteristic of the chemical substance. Variations of the concentration,temperature, and chemical substance in a chemical reaction will producevarious glazuur colors. The product development method was conducted byan experimental research in the Building Material Laboratory and theChemical Laboratory UNY. The marketing strategy runs by promotionthrough regional and national expo activities and direct selling toconsumers. The product marketing runs through PT. UNY MULTIUTAMA, the ceramic tile industry ”PWS” Godean, and Timboel KeramikKasongan.The business products of the UJI unit in UNY are categorized intothree groups: (1) glazuur materials, (2) glazuur tiles, and (3) glazuurceramics. Various glazuur colours being produced are green, blue, brown,black, grey, yellow, chromic red, lead chromic red, and oxcyde. Thebusiness product specifications having been produced are: (1) the glazuurmaterials have an added value in aesthetics because they have various brightcolors and the burning temperature is lower compared to the existingmarketed glazuur materials, (2) the glazuur tiles have more aestheticalappearance, not porous, smoother surface, and higher elastical strength andlower water absorption compared to non-glazuur materials, (3) glazuurceramics have smaller surface pores compared to non-glazuur materials so itwill not wet although they are exposed with water for 48 hours. Theliquefied test in the buffer solution with pH4 shows that there are metals inliquefied glazuur materials, but the amount is still below the threshold, so itwill not endanger the environment. Although the incubation period ofDP2M has been over, the business prospect of the glazuur material UJI unitInotek, Volume 13, Nomor 2, Agustus 2009136is predicted to succeed because of the raw material availability in relativelycheap cost but relatively high product selling values.Keywords: glazuur materials, ceramics, and tiles